Mission Mozart : Lang Lang and Nikolaus Harnoncourt a documentary by Christian Berger - Mozart, Wolfgang Amadeus 1756-1791; Mozart, Wolfgang Amadeus 1756-1791 (BFMI coproduction with ZDF, 2014)
In the Spring of 2014, Nikolaus Harnoncourt, acclaimed and world-famous early music innovator and authority, and Lang Lang, a superstar pianist of stunning virtuosity and freeƯwheeling musical instincts, took over the Wiener Musikverein for an unprecedented musical meeting-of-the-minds between two very different artists. Together with the Wiener Philharmonik Orchester, Nikolaus Harnoncourt and Lang Lang record the Mozart's Piano Concertos No. 17 in G major K. 453 and No. 24 in C minor K. 491. This film documents those recording sessions, offering revealing insight into the creative processes of two of today's most distinctive and influential musicians. Both artists found the collaboration to be rewarding. For Lang Lang, "every session with [Harnoncourt] is like a masterclass. He just gave me everything from his heart, and that direct connection in music-making is the most important inspiration for me". Nikolaus Harnoncourt reflected that, "It's rare to find someone who is so open-minded ... I can only work with soloists who are ready to develop a concept together with me, and very seldom have I experienced a reading of the work that developed so quickly.